J EPIDEMIOL PUBLIC HEALTH 2017
DOI: 10.26911/jepublichealth.2017.02.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age and Socio Economic Status on the Quality of Life of Patients with Cervical Cancer Undertaking Chemotherapy at Dr. Moewardi Hospital Surakarta

Abstract: Background: Cervical cancer is a type of cancer affecting women with high incidence and mortality in the world.Patient with cervical cancer have to undertake prolonged sequential treatment and therefore may experience physical, physicological and social changes, which may affect their quality of life. This study aimed to examine effect of age and socio economic status on the quality of life of patients with cervical cancer undertaking chemotherapy at Dr. Moewardi hospital, Surakarta. Subjects and Method: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The results of this study are in line with the research conducted by Kusumaningrum et al (2016) [14] which states that there is a significant difference in knowledge before and after peer group education in the intervention group. The average knowledge of WUS after being given education has increased compared to before being given education.…”
Section: Based On Characteristicssupporting
confidence: 92%
“…The results of this study are in line with the research conducted by Kusumaningrum et al (2016) [14] which states that there is a significant difference in knowledge before and after peer group education in the intervention group. The average knowledge of WUS after being given education has increased compared to before being given education.…”
Section: Based On Characteristicssupporting
confidence: 92%
“…Gunawan, Chondro p-ISSN 0853-7720; e-ISSN 2541-4275, Volume 9, Nomor 1, halaman 30 -37, Januari 2024 DOI : https://doi.org/10.25105/pdk.v9i1.16377 35 dimana pasien kanker membutuhkan biaya yang cukup besar untuk pengobatan. Apabila pasien tidak bekerja maka akan meningkatkan beban keuangan yang berujung pada depresi (Fadhilla et al, 2017).…”
Section: Hubungan Antara Stadium Kanker Dan Depresi Pada Pasien Kanke...unclassified
“…According to Prastiwi (2012), although treatment costs are covered by BPJS, family health insurance still faces financial difficulties, in which families need a lot of money for operating costs during a gradual and continuous medical examination as well as chemotherapy treatment (Fadhilla et al, 2017). Therefore, it can be concluded that there is financial pressure or financial burden for those who do not work in families to increase depression (Sharp et al, 2015).…”
Section: The Effect Of Occupation On the Family Incomementioning
confidence: 99%